Preregistered test of whether a virtual nose reduces cybersickness - Sai Ho Yip; Adrian K. T. Ng; Henry Y. K. Lau; Jeffrey A. Saunders (Cognitive Research, 2024)
Abstract Recent findings suggest that adding a visual depiction of a nose to virtual reality displays (virtual nose) can reduce motion sickness. If so, this would be a simple intervention that could improve the experience of a variety of VR applications. However, only one peer-reviewed study has reported a benefit from a virtual nose, and the effect was observed in a single low-powered experiment. To further test the effectiveness of a virtual nose for mitigating motion sickness in VR, we performed a preregistered experiment with higher power and better control. Subjects were presented with simulated movement in a virtual environment using a head-mounted display, and the resulting motion sickness was measured using the Fast Motion Sickness Scale (FMS) and the Simulator Sickness Questionnaire (SSQ). Conditions with and without a virtual nose were tested in separate sessions on different days, and the mean habituation effects were removed analytically. Awareness of the manipulation was assessed with a funnel debriefing procedure. The sample size (n = 32) was chosen to have over 90% power to detect the estimated effect size based on previous data (d z  = 0.6). We found no significant difference between motion sickness in conditions with and without the virtual nose. The estimated effect size was close to zero, d z = − 0.02, with a 95% credible interval [− 0.37, 0.33]. Results from a Bayesian analysis imply that any benefit from a virtual nose is unlikely to be more than a 26% reduction in FMS scores, and any cost is unlikely to be more than a 23% increase. Our results do not support the hypothesis that a virtual nose is a general and effective way to relieve motion sickness in virtual reality.